2015
DOI: 10.1016/j.jmii.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification, epidemiological relatedness, and biofilm formation of clinical Chryseobacterium indologenes isolates from central Taiwan

Abstract: Both Vitek 2 and MALDI-TOF MS methods showed good ability in the determination of C. indologenes. Among the examined drugs, minocycline was the most potent one. As many as 38.2% C. indologenes isolates showed biofilm-forming ability. PFGE analyses revealed the possible intrahospital transmission of this bacterium in central Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
2
35
2
3
Order By: Relevance
“…Patients with Chryseobacterium infections usually have comorbidities, such as cardiovascular disease, malignancy, chronic kidney disease, diabetes mellitus, and chronic obstructive pulmonary disease (3)(4)(5)(6)(7)(8)(9)(10)(11). In our study, one or more comorbidities were recognized in 81.7% of Chryseobacterium-infected patients.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Patients with Chryseobacterium infections usually have comorbidities, such as cardiovascular disease, malignancy, chronic kidney disease, diabetes mellitus, and chronic obstructive pulmonary disease (3)(4)(5)(6)(7)(8)(9)(10)(11). In our study, one or more comorbidities were recognized in 81.7% of Chryseobacterium-infected patients.…”
Section: Discussionmentioning
confidence: 50%
“…According to previous studies, Chryseobacterium commonly causes bacteremia, catheter-related infection, and pneumonia, and these infections are usually hospital acquired (3)(4)(5)(6)(7)(8)(9)(10)(11). Indeed, a previous study found that 47% (17/36) of C. indologenesinfected patients developed bacteremia (7), and in a study of 215 Chryseobacterium isolates (4), 64.2% and 18.1% were obtained from sputum and blood, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its ability to produce biofilm on foreign materials and produce proteases, can cause several forms of infections and is responsible for its virulent character 31. One study mentioned the production of a metallo-β-lactamase, which allows the bacteria to hydrolyse the β lactam part of some drugs 32.…”
Section: Discussionmentioning
confidence: 99%